Spotlight on siponimod and its potential in the treatment of secondary progressive multiple sclerosis: the evidence to date - Gajofatto A (Drug Design, Development and Therapy, 2017)
Alberto Gajofatto Department of Neuroscience, Biomedicine and Movement Sciences, University of Verona, Verona, Italy Abstract: Siponimod (BAF312) is a synthetic molecule belonging to the sphingosine-1-phosphate (S1P) modulator family, which has putative neuroprotective properties and well-characterized immunomodulating effects mediated by sequestration of B and T cells in secondary lymphoid organs. Compared to fingolimod (ie, precursor of the S1P modulators commercially available for the treatment of relapsing–remitting [RR] multiple sclerosis [MS]), siponimod exhibits selective affinity for types 1 and 5 S1P receptor, leading to a lower risk of adverse events that are mainly induced by S1P3 receptor activation, such as bradycardia and vasoconstriction. In addition, S1P1 and S1P5 receptors are expressed by neurons and glia and could mediate a possible neuroprotective effect of the drug. A Phase II clinical trial of siponimod for RR MS showed a significant effect of the active drug compared to placebo on reducing gadolinium-enhancing lesions on brain magnetic resonance imaging (MRI) after 3 months of treatment. In a recently completed Phase III trial, treatment with siponimod was associated with a significant reduction in disability progression in secondary progressive (SP) MS patients compared to placebo. In this article, current evidence supporting siponimod efficacy for SP MS is reviewed. Keywords: multiple sclerosis, siponimod, progression, disability, treatment